2021
DOI: 10.21203/rs.3.rs-189686/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression levels of caspase-3 and gasdermin E and their involvement in the occurrence and prognosis of lung cancer

Abstract: Background Pyroptosis plays a dual role in the development of cancer and malignancy, and as such, may potentially be a new target for cancer treatment. However, the inflammatory response to pyroptosis may have adverse effects on the body. The roles of gasdermin E (GSDME), caspases, and related proteins associated with pyroptosis in cancer remain controversial. This study aimed to explore whether the expression levels of caspase-3 and GSDME affect the clinical stage, pathological grade, and survival prognosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The above results indicated that GSDMD can be regard as an independent prognostic biomarker in LUAD patients. Meanwhile, the expression level of GSDME in lung cancer tissue is significantly higher than that in adjacent tissue, patients with lung cancer having a high GSDME expression have less lymph node metastasis and longer postoperative survival, although the decrease in GSDME level was not significantly correlated with tumor size, clinical stage, age, or tumor recurrence rate ( 55 , 110 ). In addition, the expression level of GSDME was positively correlated with that of caspase-3, and hence caspase-3 is also an important prognostic biomarker in lung cancer patients ( 55 ).…”
Section: The Role Of Pyroptosis In Nsclc Therapymentioning
confidence: 94%
See 1 more Smart Citation
“…The above results indicated that GSDMD can be regard as an independent prognostic biomarker in LUAD patients. Meanwhile, the expression level of GSDME in lung cancer tissue is significantly higher than that in adjacent tissue, patients with lung cancer having a high GSDME expression have less lymph node metastasis and longer postoperative survival, although the decrease in GSDME level was not significantly correlated with tumor size, clinical stage, age, or tumor recurrence rate ( 55 , 110 ). In addition, the expression level of GSDME was positively correlated with that of caspase-3, and hence caspase-3 is also an important prognostic biomarker in lung cancer patients ( 55 ).…”
Section: The Role Of Pyroptosis In Nsclc Therapymentioning
confidence: 94%
“…Compared to paired normal lung tissues, the expressions of GSDME, caspase-3, and caspase-8 were significantly were increased in most lung cancer tissues, and GSDME was mainly found in the cytoplasm and a small amount in the cell membrane in lung cancer tissues. However, the level of GSDME was positively correlated with the postoperative survival rate of patients with lung cancer ( 55 ). Similarly, GSDME was modestly upregulated in EGFR-mutant, and downregulation in serine/threonine kinase 11 (STK11)- or Kelch-like ECH-associated protein 1 (KEAP1)/Nuclear factor (erythroid-derived 2)-like 2 (NFE2L2)-mutant in LUAD patients based on the TCGA dataset.…”
Section: Pyroptosis In Nsclc-associated Signaling Pathwaysmentioning
confidence: 99%